Dakwah Dengan Seni Musik: Studi Pada Grup Qosidah Modern At-Tarbiyah Putri Cilendek Cibeureum Kota Tasikmalaya - Muhamad Hanif Fuadi; Salman Alfarisi; Dwi Nur Prakoso (Jurnal Bimbingan Penyuluhan Islam, 2022)
This research reveals interesting things from the phenomenon ofda'wah with the art of music as a means to attract mad'u, especiallyyoung people. Da'wah and the art of music both have a mutuallybeneficial relationship. Da'wah as an effort to call for goodness whilethe art of music makes beauty in calling for goodness. The QasidahModern At-Tarbiyah Putri Cilendek Cibeureum Group, KotaTasikmalaya, which was founded by Hj. Siti Habibah (Alm) as anexample in conveying da'wah messages decorated with music. The this group continues to exist due to empowerment in the economicsector for members.progress of the times is a step to innovate in the development ofda'wah and music, so that song lyrics as a means of preaching, youngpeople as targets of propaganda and even for group personnelbecome a means of propaganda in the field of economicempowerment. This research uses a qualitative approach as an effortto uncover the meaning behind its establishment and activities fromstage to stage at the Qasidah Modern At-Tarbiyah Putri CilendekCibeureum Group, Tasikmalaya City. Field observations, in-depthinterviews and documentation became the methods in this study. Theresult of this reserch reveal a deep philosophy in carrying out da'wahamidst the progress of the times, presenting modern music as themedium, then da'wah messages are mixed into song lyrics so thatIslamic values are embedded in young people and on the other hand dakwah dan musik, sehingga lirik lagu sebagai sarana dakwah, kawula muda sebagai sasaran dakwah bahkan untuk personil grup mejadi sarana dakwah di bidang pemberdayaan ekonomi. Penelitian ini menggunakan pendekatan kualitatif sebagai upaya mengungkap makna dibalik berdirinya serta kegiatan dari panggung ke panggung Grup Qasidah Modern At-Tarbiyah Putri Cilendek Cibeureum Kota Tasikmalaya. Observasi lapangan, wawancara mendalam dan dokumentasi menjadi metode dalam penelitian ini. Hasil dari penelitian ini terungkap suatu filosofi mendalam dalam melaksanakan dakwah ditengah kemajuan zaman, mengadirkan musik modern sebagai medianya, kemudian pesan dakwah yang diramu ke dalam lirik lagu supaya tertanam dalam diri kawula muda nilai keislaman serta disisi lain grup ini tetap eksis disebabkan oleh pemberdayaan bidang ekonomi untuk anggota. Kata Kunci: Qasidah, musik, dakwah Abstract This research reveals interesting things from the phenomenon of da'wah with the art of music as a means to attract mad'u, especially young people. Da'wah and the art of music both have a mutually beneficial relationship. Da'wah as an effort to call for goodness while the art of music makes beauty in calling for goodness. The Qasidah Modern At-Tarbiyah Putri Cilendek Cibeureum Group, Kota Tasikmalaya, which was founded by Hj. Siti Habibah (Alm) as an example in conveying da'wah messages decorated with music. The progress of the times is a step to innovate in the development of da'wah and music, so that song lyrics as a means of preaching, young people as targets of propaganda and even for group personnel become a means of propaganda in the field of economic empowerment. This research uses a qualitative approach as an effort to uncover the meaning behind its establishment and activities from stage to stage at the Qasidah Modern At-Tarbiyah Putri Cilendek Cibeureum Group, Tasikmalaya City. Field observations, in-depth interviews and documentation became the methods in this study. The result of this reserch reveal a deep philosophy in carrying out da'wah amidst the progress of the times, presenting modern music as the medium, then da'wah messages are mixed into song lyrics so that Islamic values ​​are embedded in young people and on the other hand this group continues to exist due to empowerment in the economic sector for members. Keywords: Qasidah, music, da'wah [1] Institut Nahdlatul Ulama Tasikmalaya [2] Institut Nahdlatul Ulama Tasikmalaya